Ensino semipresencial em cursos superiores presenciais: legislação, conceitos e reflexões - Oliveira, Adriana Tavares de (2012)
The present study aims to reflect about the use of information and communication technologies in higher level education, more precisely at the use of blended-learning activities in face-to-face university courses. The reflection was supported by a thorough bibliographic survey of academic scientific productions (theses and dissertations) related to blended-learning in CAPES database and a documental case study analysis of a private higher education institution. The results obtained from the literature, together with the case study analysis, indicate the growth of blended-learning activities in higher education face-to-face courses, based on Ordinances 2253 launched in 2001, and 4059 launched in 2004. The data indicate that this increase shows different interpretations of legislation, which generates several ways of implementing blended-learning. Thus research involving this issue show different approaches and concerns, and the academic scientific survey and the case study analysis show experiences that seem not to have similar characteristics. The conclusion reached is that the little time span from the first ordinance, Ordinance 2253 of 2001, and the combination of distance and face-to-face education aspects can generate specific characteristics of blended-learning in each university institution. Nevertheless, constant use in digital information and communication technologies presented in our research data reveal a trend in convergence of face-to-face and distance education modalities